How Important of Students' Literacy and Numeracy Skills in Facing 21st-Century Challenges: A Systematic Literature Review - Deda, Yohanis Ndapa; Disnawati, Hermina; Daniel, Otaget (Universitas Pendidikan Ganesha, 2023)
Literacy Numeracy skills (LNS) are fundamental for facing global challenges in the 21st century. LNS can help people achieve their goals. However, there has not been a thorough study on literacy and numeracy research. To improve the quality of literacy and numeracy research, researchers must study much literature for further analysis. This research aims to analyze students' literacy and numeracy skills in facing 21st-century challenges. The research method used is the Systematic Literature Review to read 27 documents by searching for the keywords